Perceived value drives use of routine asymptomatic surveillance PET/CT by physicians who treat head and neck cancer. Issue 5 (10th January 2020) - Roman, Benjamin R.; Lohia, Shivangi; Mitra, Nandita; Wang, Marilene B.; Pou, Anna M.; Holsinger, F. Christopher; Myssiorek, David; Goldenberg, David; Asch, David A.; Shea, Judy A.
Abstract: Background: Why physicians use surveillance imaging for asymptomatic cancer survivors despite recommendations against this is not known. Methods: Physicians surveilling head and neck cancer survivors were surveyed to determine relationships among attitudes, beliefs, guideline familiarity, and self‐reported surveillance positron‐emission‐tomography/computed‐tomography use. Results: Among 459 responses, 79% reported using PET/CT on some asymptomatic patients; 39% reported using PET/CT on more than half of patients. Among attitudes/beliefs, perceived value of surveillance imaging (O.R. 3.57, C.I. 2.42‐5.27, P = <.0001) was the strongest predictor of high imaging, including beliefs about outcome (improved survival) and psychological benefits (reassurance, better communication). Twenty‐four percent of physicians were unfamiliar with guideline recommendations against routine surveillance imaging. Among physicians with high perceived‐value scores, those less familiar with guidelines imaged more (O.R. 3.55, C.I. 1.08‐11.67, P = .037). Conclusions: Interventions to decrease routine surveillance PET/CT use for asymptomatic patients must overcome physicians' misperceptions of its value. Education about guidelines may modify the effect of perceived value.